2005
DOI: 10.1021/la046983l
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Mechanism of Photocatalytic Degradation of the Bacterial Wall Membrane at the TiO2 Interface by ATR-FTIR and Laser Kinetic Spectroscopy

Abstract: The photocatalytic peroxidation of E. coli cell, lipo-polysaccharide (LPS), phosphatidyl-ethanolcholine (PE), and peptidoglycan (PGN) of the E. coli membrane wall has been investigated on TiO2 porous films by ATR-FTIR spectroscopy. The fast reactions of the photogenerated charge carriers in TiO2 with E. coli, LPS, and PE were monitored by laser kinetic spectroscopy. ATR-FTIR spectroscopy allowed the identification of E. coli, LPS, PE, and PGN as photocatalytic peroxidation products. The PGN was observed to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
224
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 303 publications
(241 citation statements)
references
References 35 publications
15
224
0
2
Order By: Relevance
“…Recently, we have reported the mechanism of the damage induced by TiO 2 photocatalysis on the bilayer cell-envelope of Escherichia coli in several studies [20][21][22][23]. Other groups working in the disinfection field have also addressed the mechanism of disinfection [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported the mechanism of the damage induced by TiO 2 photocatalysis on the bilayer cell-envelope of Escherichia coli in several studies [20][21][22][23]. Other groups working in the disinfection field have also addressed the mechanism of disinfection [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation is widely accepted as the damage pathway caused by RSs attack. MDA, a product of lipid peroxidation, was used to indicate this oxidative process [13,16,32,33]. Fig.…”
Section: Mechanism Of Membrane Destructionmentioning
confidence: 99%
“…31 The nucleic acid bands were observed near 1240 cm -1 , overlapping with the asymmetric stretching mode νas(PO 2-) of the phospholipid phospho-diester. 32 Moreover, the peak of 1088 cm -1 was assigned to the vibrations of the sugar rings of lipopolysaccharides. With the irradiation time increasing, all of these characteristic peaks significantly decayed in intensity or even disappeared, which indicated that the reactive species sterilize bacteria and lead to leakages of the carboxylic acid during the photoelectrocatalysis process.…”
Section: Antibacterial Testmentioning
confidence: 99%
“…[3][4][5][6] TiO2-based photocatalysts have been used to inactivate bacteria, viruses, and cancer cells. [7][8][9][10][11][12] However, the wide band gap (3.2 eV) of TiO2 means it can only absorb spectrum in the near-UV region, which limits its, practical applications for photocatalytic inactivation of bacteria. There is thus a need to enhance the absorption capability of bactericidal materials in the visible region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation